Nutritional deficiencies in low-sociodemographic-index countries: a population-based study - Li, Huansong; Ren, Huiming; Guo, Xu; Chen, Zhu (Frontiers in Nutrition, 2023)
Background We aimed to estimate the burden of nutritional deficiency according to sex and age in countries with a low sociodemographic index (SDI). Methods Following the methods of the Global Burden of Diseases, Injuries, and Risk Factors Study 2019, estimated annual percentage changes (EAPCs) were calculated to determine trends in the age-standardized rates of incidence and disability-adjusted life-years (DALYs) of nutritional deficiency and its main subcategories from 1990 to 2019 in low-SDI countries. Findings From 1990 to 2019, the age-standardized incidence and DALY rates of nutritional deficiency showed decreasing trends, with EAPCs of −0.90 [95% confidence interval (CI), 1.06 to −0.75] and −3.20 (95% CI, −3.29 to −3.10), respectively, in low-SDI countries. In 2019, of the subcategories analyzed, vitamin A deficiency had the highest age-standardized incidence rate and protein–energy malnutrition had the highest age-standardized DALY rate. From 1990 to 2019, the greatest decrease in the age-standardized incidence rate was observed for vitamin A deficiency and the greatest decrease in the age-standardized DALY rate was observed for protein–energy malnutrition. At the national level, from 1990 to 2019, the greatest increase in the age-standardized incidence rate of overall nutritional deficiency was observed in males in Afghanistan (EAPC: 0.28; 95% CI, 0.07 to 0.49). Of the age groups analyzed, the highest incidence and DALY rates of overall nutritional deficiency and dietary iron deficiency were observed in children aged 1–4 years. Interpretation The age-standardized incidence and DALY rates of nutritional deficiency decreased significantly from 1990 to 2019, especially for vitamin A deficiency and protein–energy malnutrition. Overall nutritional deficiency and dietary iron deficiency occurred primarily in children aged 1–4 years.